2021
DOI: 10.1177/13591045211033186
|View full text |Cite
|
Sign up to set email alerts
|

A survey of mental health professionals in a paediatric hospital during COVID-19

Abstract: Background There is little understanding of the mental health impact for young people with long-term physical health conditions and mental health professionals’ experiences of supporting them during COVID-19. This service evaluation aimed to conduct a survey of the psychological services provided by mental health professionals in a paediatric hospital in relation to COVID-19. Method Clinical psychologists and assistant psychologists ( n = 76) across the hospital were asked to complete a survey, asking about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This pragmatic pilot suggests the highly accessible intervention can be offered to patients on waiting lists for mental health treatment. This is relevant to children services during COVID-19, as we have seen an uptake in technology use to maintain service provisions (Ching et al, 2021; Sharma et al, 2020). A recent trial found that a digital SSI improved mental health outcomes of students during COVID-19 (Wasil et al, 2021) suggesting that SSIs are especially useful when access to care is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This pragmatic pilot suggests the highly accessible intervention can be offered to patients on waiting lists for mental health treatment. This is relevant to children services during COVID-19, as we have seen an uptake in technology use to maintain service provisions (Ching et al, 2021; Sharma et al, 2020). A recent trial found that a digital SSI improved mental health outcomes of students during COVID-19 (Wasil et al, 2021) suggesting that SSIs are especially useful when access to care is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the pandemic on mental health has been less studied than the COVID-19 epidemiology, transmission patterns, physical symptoms, and their treatment [18]. Furthermore, while numerous studies have been conducted to assess physician and patient satisfaction with telemedicine [19][20][21][22], to our knowledge, fewer studies have been conducted to examine physicians' perceptions of the mental health crisis and/or suggestions on how to best face the future challenges [1,[23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent survey of mental health professionals captured an initial picture of the mental health landscape in the paediatric population, finding diverse experiences of the impact of COVID-19 on working, on children, and on families (Ching et al, 2021). Our own clinical experience has also been heterogeneous.…”
mentioning
confidence: 99%
“…Mental health in paediatric patients attending a children's hospital may have been compromised by the COVID-19 pandemic but flexibility in service provision has allowed needs to be met, in terms of the number of families referred to our service that continued to receive remote assessment and intervention. Based on our personal clinical judgement and experiences of working during the pandemic and preliminary research (e.g., Ching et al, 2021), some of these service delivery adaptations appear beneficial to families and staff and may be continued post-pandemic.…”
mentioning
confidence: 99%